Adjustment Processes After the First Wave of the COVID-19 Pandemic: A Grounded Theory Study Based on Clinical Psychologists’ Experience - Lamiani, Giulia; Borghi, Lidia; Bonazza, Federica; Rebecchi, Daniela; Lazzari, David; Vegni, Elena (Frontiers in Psychology, 2022)
Background. Anxiety, depression, and post-traumatic stress have been reported among the general population during the first wave of the COVID-19 pandemic. However, the adjustment after the emergency phase remains under-investigated. This study aims to understand the adjustment processes of the population after the emergency phase of the pandemic. Methods. We conducted a grounded theory based on the experience of 24 clinical psychologists who provided extensive support to the population during the pandemic in different Italian regions. Three online focus groups were conducted. The transcripts of the focus groups were analyzed through a process of open, axial, and selective coding. Data collection terminated once thematic saturation was reached. Results. Repositioning emerged as the evolutionary task people were confronted with, in the face of a New Reality. Repositioning meant dealing with and integrating unpleasant Emotional Experiences deriving from the lockdown and reopening (i.e., unsafety, emotional exhaustion, loneliness, uncertainty, loss, and disconnection) through different Coping Strategies. Repositioning was facilitated or hindered by contextual and individual Intervening Conditions and led to two Adjustment Outcomes: growth or block. Conclusions. Results suggest that repositioning was the core task people had to face after the emergency phase of COVID-19. Proactive psychological interventions may support the population in repositioning in order to prevent maladjustment and encourage post-traumatic growth.